THE BIRD AERODINAMICS IN THE QUR'á¾¹N (The Qur'anic Verses Study of Birds Aviation Mechanics) - Habibullah, Ilham; Puspitasari, Niken Sylvia (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This article talks about a flight of birds in the Qur'Än. Because most of words refer to birds in the Qur'Än has not, thematically, researshed yet. So that our knowledge of bird phenomenon restricted to saintific research. Therefore this research aimed, thematically, to reveal how tafsir studies explain the bird phenomenon. After analitical and descriptical reviewing, we revive that Allah holds wing of birds by His power to make them flying. As we know, tafsir stidies, especially tafsir ilmiy are, further, necessary to be developed. Because aerodinamic theory just explained emirically and rasionally aspect. Therefore, it necessary need to integrate betwen tafsir studies and scientific research to qur`anic contemplating.